Lactoferrin-tethered betulinic acid nanoparticles promote rapid delivery and cell death in triple negative breast and laryngeal cancer cells. Issue 1 (1st January 2020) - Halder, Asim; Jethwa, Megha; Mukherjee, Pritha; Ghosh, Subarna; Das, Suvadra; Helal Uddin, A. B. M.; Mukherjee, Arup; Chatterji, Urmi; Roy, Partha
Abstract: Cancer management presents multifarious problems. Triple negative breast cancer (TNBC) is associated with inaccurate prognosis and limited chemotherapeutic options. Betulinic acid (BA) prevents angiogenesis and causes apoptosis of TNBC cells. NIH recommends BA for rapid access in cancer chemotherapy because of its cell-specific toxicity. BA however faces major challenges in therapeutic practices due to its limited solubility and cellular entree. We report lactoferrin (Lf) attached BA nanoparticles (Lf-BAnp) for rapid delivery in triple negative breast (MDA-MB-231) and laryngeal (HEp-2) cancer cell types. Lf association was confirmed by SDS-PAGE and FT-IR analysis. Average hydrodynamic size of Lf-BAnp was 147.7 ± 6.20 nm with ζ potential of −28.51 ± 3.52 mV. BA entrapment efficiency was 75.38 ± 2.70% and the release mechanism followed non-fickian pattern. Impact of Lf-BAnp on cell cycle and cytotoxicity of triple negative breast cancer and its metastatic site laryngeal cancer cell lines were analyzed. Lf-BAnp demonstrated strong anti-proliferative and cytotoxic effects, along with increased sub-G1 population and reduced number of cells in G1 and G2 /M phases of the cell cycle, confirming reduced cell proliferation and significant cell death. Speedy intracellular entry of Lf-BAnp occurred within 30 min. Lf-BAnp design was explored for the first time as safer chemotherapeutic arsenals against complex TNBC conditions. GRAPHICAL ABSTRACT: UF0001